Moldova Financial Sector Assessment Program : Core Principles for Effective Deposit Insurance Systems - World Bank (Washington, DC, 2015)
During February 17 to March 5, 2014 an assessment under the international monetary fund (IMF) and World Bank financial sector assessment program (FSAP) was conducted for the Republic of Moldova. As part of the FSAP, the deposit insurance system was assessed against the Basel committee on banking supervision (BCBS) - International Association of Deposit Insurers (IADI) core principles for effective deposit insurance systems. The team found the deposit guarantee fund (DGF) is compliant or largely compliant with 12 out of 17 applicable core principles, materially non-compliant with 4 core principles and non-compliant with one. This report presents review of the background and structure of the DGF, a review of preconditions for effective deposit insurance systems, a summary of key findings and recommendations, and a section providing the detailed assessment of the core principles.